Social criticisms of marketing: concerns and initiatives. (3rd June 2019) - Mandal, Pratap Chandra
Companies adopt marketing practices to satisfy customers, develop relationships, and generate revenues and profits. However, sometimes marketers focus on their selfish motives forgetting about customer welfare and welfare of the society. Marketers are often criticised for the negative impact of their practices on customers. Such practices include high prices of products, high distribution costs, high advertising and promotion costs, excessive mark-ups, deceptive practices, high-pressure selling, questionable products, planned obsolescence, and poor service to disadvantaged customers. Marketers are criticised for creating false wants and materialism, scarcity of social goods, and cultural pollution. Critics worry about marketers harming competitors and reducing competition. In this age of social marketing, marketers should consider societal concerns of various stakeholders. Companies should maintain a proper balance between societal requirements and their own objectives of generating revenues and profits. This will help companies to develop fruitful customer relationships and have a sustainable growth.